Pembentukan Karakter Melalui Pendidikan Agama Islam - Jaelani, Jaelani (CV. Publikasi Indonesia, 2022)
Character education is an important aspect of implementing learning in any field. However, this character education needs to be formed, one of which is Islamic religious education. Writing this article aims to determine the formation of character through Islamic religious education. This study uses a literature review research method while data collection techniques are carried out by exploring journals and other information relevant to the study. The results show that character building through Islamic religious education is formed through learning aqidah as a religious basis, learning the Koran and hadith as a way of life, learning fiqh as a legal guide in worship, learning history to implement exemplary life, and learning morals as a guide for good behavior or bad. The conclusion of this study is that individuals must familiarize themselves with carrying out teachings that are in harmony with Islamic teachings in order to have a wise personality, the basic framework of Islam includes Akidah, Shari'ah, and morals.